THE EFFECTS OF PREHEAT AND FILLER BUFFER LAYER ON THE MATERIALS OF ASTM A36 IN THE HARDFACING OVERLAY WELDING TO THEIR HARDNESS AND METALLOGRAPHY - Mohammad Afif Hamdani; Dika Anggara; Rikat Eka Prastyawan (Surabaya State Polytechnic of Shipbuilding, 2024)
ASTM A36 steel overlay products have been used by the industry as liners to protect the main material from abrasion attacks that will occur. From the background above, the formulation of the problem can be written